If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-8 + 8k) = -192 (-8 * 8 + 8k * 8) = -192 (-64 + 64k) = -192 Solving -64 + 64k = -192 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + 64k = -192 + 64 Combine like terms: -64 + 64 = 0 0 + 64k = -192 + 64 64k = -192 + 64 Combine like terms: -192 + 64 = -128 64k = -128 Divide each side by '64'. k = -2 Simplifying k = -2
| 4c-2(x-3)=-2+5x-10 | | 16+8=40 | | 6-6x+5x=13 | | (m-n+k)(m+7n-6k)=0 | | 4(-2+8n)=-136 | | X+2x+7x+9x+1=42 | | 14=21b | | 4(3-2x)=3(2-3x) | | -8=-2n | | -50=5d | | 135=-9k | | 3/4*x=2/7 | | 25x+71=156 | | 4(7x+8)+x=206 | | 2t=lb | | 6r=60 | | 3x+1+58x+33x=115 | | 75s=195 | | 2(-3)+2(-1)-(-3)(-1)+21= | | 3x+1+58x+13x=115 | | x(9+8)=33 | | =11.6 | | Y/3-3=-11 | | 12x+3=3(2x+6) | | 405.36=230+0.64x | | u+6u=14 | | -9+3v=v+3 | | x-3=-3-10x+7x | | -13+5x=x-1 | | 10n+15=9n+6n | | (3x^3/z)^3 | | 6x+21=7(x+3) |